"Weight of evidence" as a tool for evaluating disease in wildlife: An example assessing parasitic infection in Northern bobwhite (Colinus virginianus). (December 2020) - Henry, Cassandra; Brym, Matthew Z.; Skinner, Kalin; Blanchard, Kendall R.; Henry, Brett J.; Hay, Alyssa L.; Herzog, Jessica L.; Kalyanasundaram, Aravindan; Kendall, Ronald J.
Abstract: The potential of parasites to affect host abundance has been a topic of heated contention within the scientific community for some time, with many maintaining that issues such as habitat loss are more important in regulating wildlife populations than diseases. This is in part due to the difficulty in detecting and quantifying the consequences of disease, such as parasitic infection, within wild systems. An example of this is found in the Northern bobwhite quail ( Colinus virginanus ), an iconic game bird that is one of the most extensively studied vertebrates on the planet. Yet, despite countless volumes dedicated to the study and management of this bird, bobwhite continue to disappear from fields, forest margins, and grasslands across the United States in what some have referred to as "our greatest wildlife tragedy". Here, we will discuss the history of disease and wildlife conservation, some of the challenges wildlife disease studies face in the ever-changing world, and how a "weight of evidence" approach has been invaluable to evaluating the impact of parasites on bobwhite in the Rolling Plains of Texas. Through this, we highlight the potential of using "weight of the evidence" to better understand the complex effects of diseases on wildlife and urge a greater consideration of the importance of disease in wildlife conservation. Graphical abstract: Image 1 Highlights: Wildlife disease has gained increased recognition as a potentially significant mechanism affecting animal populations. Global change associated with anthropogenic factors may increase the intensity and proliferation of wildlife diseases. Disease effects may be discreet and contextually dependent, confounding efforts to quantify their impacts. A weight of the evidence (WOE) approach evaluates and integrates multiple lines of evidence to identify causal factors. WOE may provide an effective means to discern significant disease impacts, setting foundations for further empirical study.